2020
DOI: 10.1177/0890334419888715
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of On-Campus Lactation Spaces for Student-Parents

Abstract: Background: Numerous researchers have evaluated the influence of federal and workplace lactation policies on breastfeeding duration, however few have considered the experiences of breastfeeding people returning to school. Research aim: The aim of this study was to evaluate the availability, accessibility, acceptability, and quality of existing on-campus lactation spaces. Methods: In-depth interviews were conducted with student-parents ( N = 18) who had expressed milk on campus. Data collection and thematic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
3
0
5
Order By: Relevance
“…Our project implementation strategies align closely with other research and calls to action (Albrecht et al, 2017;Ladores et al, 2019). Some research has called for university leaders at all levels to be vocal champions for lactation support and involved in identifying multilevel solutions, which is congruent with our implementation findings (Bostick et al, 2016;Ladores et al, 2019;Sturtevant et al, 2020). However, even when there is a lack of structural support and administrative buy-in for lactation initiatives, this project supports that student organizations and lactating parents themselves can utilize similar grassroots strategies to research, advocate for, and improve the campus lactation environment.…”
Section: > > Discussionsupporting
confidence: 79%
“…Our project implementation strategies align closely with other research and calls to action (Albrecht et al, 2017;Ladores et al, 2019). Some research has called for university leaders at all levels to be vocal champions for lactation support and involved in identifying multilevel solutions, which is congruent with our implementation findings (Bostick et al, 2016;Ladores et al, 2019;Sturtevant et al, 2020). However, even when there is a lack of structural support and administrative buy-in for lactation initiatives, this project supports that student organizations and lactating parents themselves can utilize similar grassroots strategies to research, advocate for, and improve the campus lactation environment.…”
Section: > > Discussionsupporting
confidence: 79%
“…Dos 15 artigos selecionados para a revisão, 10 possuíam como objetivo analisar o apoio das Instituições de ensino superior a estudantes nutrizes. (Nkrumah & Gbagbo, 2018;Bostick et al, 2016;Al-Imari et al, 2019;Spatz, 2019;Dinour et al, 2020;Bai et al, 2016;Sturtevant et al, 2019;Adcock et al, 2019;Dinour et al, 2015;Anderson et al, 2019). Tais artigos, levantaram a discussão sobre a carência de espaços adequados nos Campus universitários para as estudantes nutrizes amamentarem e realizarem a ordenha das mamas.…”
Section: Resultsunclassified
“…The literature regarding lactating university students is limited, but what is available reveals similar challenges between lactating employees and lactating university students (Burns & Triandafilidis, 2019). Employee challenges include little or no managerial support, not enough time for breaks, inadequate space for expressing milk, and not enough privacy (Sturtevant et al, 2021; Valizadeh et al, 2018). According to Cohen (2021), lactation justice is a component of equity law and reproductive rights in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The United States Fair Labor Standards Act requires employers to provide sufficient break time for an employee to express their milk in a private place other than a bathroom. Researchers examining access to workplace lactation accommodations found that women with both adequate break time and privacy were twice as likely to be breastfeeding exclusively at 6 months compared to women without access to these accommodations (Barraza et al, 2020; Sturtevant et al, 2021). These are just four examples demonstrating the importance of a policy in shaping breastfeeding outcomes.…”
Section: Introductionmentioning
confidence: 99%